STUDI ANALISA TEBAL PERKERASAN KAKU PADA RUAS JALAN KAMPUNG DATAH BILANG - LUTAN DI KABUPATEN MAHAKAM ULU - RAD, MU (KURVA S JURNAL MAHASISWA, 2018)
Roads are one of the land transportation infrastructure that has an important role for human life. In addition to geometric road planning, road pavement is part of road planning that must be planned effectively and efficiently, because the road service level requirements are higher. Kampung Datah Bilang – Lutan Road Section is one part of the collector's road that connects the sub-district and TransProvince Roads, which until now are very much expected to be developed. The construction of this road using rigid pavement, so that the pavement is resistant until its service life, it needs the right design method in its planning. There are many methods for designing the thickness of this concrete plate, including using the Bina Marga 2013 method and AASHTO 1993. In this thesis, the aim is to analyze the alternative thick design of pavement to examine the planning parameters of both methods, plan the thickness of the concrete slab, and analyze the comparative results of the two methods. This method begins with the collection of secondary data in the form of traffic data, land data and hydrological data, then calculating the thickness of the hardness using both methods. In planning the calculation of plate thickness, the input parameters for each method are needed. The input parameters for pavement thickness planning for the Bina Marga 2013 method are traffic parameters, subgrade, sub base course, sub base course of grained material, and concrete strength. The input parameters for pavement thickness planning for the 1993 AASHTO method are traffic parameters, subgrade modulus, pavement construction material, realibility, and drainage coefficient. For the case study of Kampung Datah Bilang – Lutan Road Section the concrete slab thicker based on the Bina Marga 2013 method calculation was 28,5 cm, while based on the 1993 AASHTO method was 17 cm. The difference obtained is quite large, namely 11,5 cm. This is due to differences in the input parameters of each method.